Moisture Ingress of Cemented Basecourse - Yeo, Yang sheng; Jitsangiam, Peerapong; Nikraz, Hamid (Australian Geomechanics Society, 2011)
Moisture ingress is a primary catalyst for pavement damage and plays a key role in the performance of pavement materials in service. This is evident from the issues faced as a result of high moisture sensitivity of crushed rocks used in the construction of Kwinana Freeway in Western Australia. Cement treatment is deemed a potential solution to reduce moisture sensitivity. The moisture ingress into cement treated crushed rocks can be based on the unsaturated flow theory and quantified with the term Sorpitivity, S, i.e. the square root rate of inflow volume. The linearity of the Sorptivity when plotting inflow volume against the square root of time, t0.5 also provides an indication of the homogeneity of the material. This paper assessed the Sorptivity of cement treated crushed rocks based on results from the Tube Suction Test procedures developed by Texas Department of Transportation (TxDOT). The tests shows that Sorpitivity decreases with the increase in cement content which means that higher cement content reduces the moisture sensitivity of pavements. The Sorpitivity also showed a high least-square regression of R2 > 0.9, which indicates that the materials are homogeneous.